REPORT OF THE 1958 PRESIDENT. - Niswonger, C. Rollin (The Accounting Review, 1959)
Abstract During the past year, in 1958, the activities of the Association followed the customary pattern of completion of some projects carried over from earlier years and launching new projects and programs. An exact measurement of progress is neither possible nor necessary. Each year represents only a small segment of the continuing stream of influence on accounting education and research fostered by the Association. The periodical "The Accounting Review," continued to hold its high place in accounting literature and to grow in circulation and influence. The Association has continued its policy of cooperation and cordial relationships with other accounting organizations. Recognition of varying points of view was encouraged by the appointment of non-teaching members to various Association committees. A Committee on By-Laws was appointed during 1958 to consider the creation of the office of president-elect. The recommendations of the committee were approved by the Executive Committee and presented to the members at the annual business meeting for consideration. The establishment of a special fund for a doctoral fellowship program was announced at the annual convention in Syracuse.